Ozone and UV radiation over southern South America: Climatology and anomalies - Diaz, Susana Beatriz; Camilión, C.; Deferrari, Guillermo Alejandro; Fuenzalida, H.; Armstrong, R.; Booth, C.; Paladini, Alejandro Alberto; Cabrera, S.; Casiccia, C.; Lovengreen, C.; Pedroni, J.; Rosales, A.; et al. (Photochemistry and Photobiology)
Ozone and UV radiation were analyzed at eight stations from tropical to sub-Antarctic regions in South America. Ground UV irradiances were measured by multichannel radiometers as part of the Inter American Institute for Global Change Radiation network. The irradiance channels used for this study were centered at 305 nm (for UV-B measurements) and 340 nm (for UV-A measurements). Results were presented as daily maximum irradiances, as monthly averaged, daily integrated irradiances and as the ratio of 305 nm to 340 nm. These findings are the first to be based on a long time series of semispectral data from the southern region of South America. As expected, the UV-B channel and total column ozone varied with latitude. The pattern of the UV-A channel was more complex because of local atmospheric conditions. Total column ozone levels of <220 Dobson Units were observed at all sites. Analysis of autocorrelations showed a larger persistence of total column ozone level than irradiance. A decreasing cross-correlation coefficient between 305 and 340 nm and an increasing cross-correlation coefficient between 305 nm and ozone were observed at higher latitudes, indicating that factors such as cloud cover tend to dominate at northern sites and that ozone levels tend to dominate at southern sites. These results highlight the value of long-term monitoring of radiation with multichannel radiometers to determine climatological data and evaluate the combination of factors affecting ground UV radiation. Fil: Diaz, Susana Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Camilión, C. Centro Austral de lnvestigaciones Cientifica; Argentina Fil: Deferrari, Guillermo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Fuenzalida, H. Universidad de Chile; Chile Fil: Armstrong, R. Universidad de Puerto Rico; Puerto Rico Fil: Booth, C. Biospherical Instruments Inc.; ...